Murder book - Perry, Thomas, 1947- (The Mysterious Press, 2023)
When his ex-wife asks him to investigate a sudden crime wave in the Mid-West, Harry Duncan quickly finds himself in conflict with a violent syndicate that targets both him and his ex.